THE ENTREPRENEURIAL ADMINISTRATIVE SKILLS NEEDED BY SELF-EMPLOYED MOTOR VEHICLE MECHANICS IN THE NORTH CENTRAL STATES OF NIGERIA - M, Abdulkadir; Ma’aji, S A; Salami, K A; Okwori, R O (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
This study was designed to discover the entrepreneurial administrative skills needed by self-employed motor vehicle mechanics in the North-Central States of Nigeria. The researchers formulated a research question and a null hypothesis guided the study. A descriptive survey research design was employed for the study. The study was carried out in the North-Central States of Nigeria. The targeted population for the study was 22,523 respondents comprising of 21,340 registered self-employed motor vehicle mechanics, 1,016 managers of micro firms in motor vehicle mechanics and 167 entrepreneurship lecturers. A multi-stage sampling technique was employed for the study. The purposive sampling procedure was employed to select three states including Federal Capital Territory, Abuja out of seven states that constitute the North-Central geopolitical zone of Nigeria. The sample for the study was 2,019 respondents comprising of 1,435 registered self-employed motor vehicle mechanics, drawn through the use of Taro Yamane formula for finite population, 475 managers of micro firms in motor vehicle mechanics and 109 entrepreneurship lecturers. A structured questionnaire titled: Self-Employed Motor Vehicle Mechanics Entrepreneurial Administrative Skills Needed Questionnaire (SEMVMEASNQ) developed by the researchers was used for data collection. The instrument was validated by five Lecturers in the Department of Industrial and Technology Education, the Federal University of Technology, Minna and the reliability coefficient of instrument was 0.84 through Cronbach Alpha Statistics. Mean and standard deviation were the statistical tools used to analyze the data for answering the research question; while One-Way Analysis of Variance (ANOVA) statistics was employed to test the null hypothesis for the study at .05 level of significance. The findings of the study revealed among others that all the 31 items entrepreneurial administrative skills are highly needed by motor vehicle mechanics for self-employment in the North Central States of Nigeria. Based on the findings it was recommended among others that: the National Council on Automotive (NCA) should in collaboration with the Federal Ministry of Labour and Productivity incorporate the identified entrepreneurial skills into their training and re-training programs so that motor vehicle mechanics can be made to acquire the needed entrepreneurship management skills that will assist them to sustain and secure their employment.